On the Mechanism for the Collective Acceleration of Ions at the Spark Stage of a Vacuum Discharge; 1-st International Congress on Radiation Physics, High Current Electronics, and Modification of Materials; Vol. 2: 12-th Simposium on High Current Electronics - Barengolts S. A. (2000, 2000)
A model of the collective acceleration of ions at the spark stage of a vacuum discharge has been proposed which is based on the ecton mechanism for the operation of a cathode spot and on the idea of a deep nonstationary potential well. The possibility a deep potential well being formed in the presence of an external electric field has been demonstrated and the prerequisites for its appearance in an explosive-emission diode have been revealed. The proposed model provides an explanation for the principal processes leading to collective acceleration of ions; its predictions are in good agreement with experimental results